ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PENGGUNA SOFTWARE AKUNTANSI DAN DAMPAKNYA TERHADAP KINERJA INDIVIDU (STUDI PADA PT PETROKIMIA KAYAKU PEMAKAI SOFTWARE AKUNTANSI SEVENTHSOFT ) - Rozi, Ahmad Fahrul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims to examine the factors that affect user satisfaction on the individual performance of users of accounting software program packages, especially Sefensofth Accounting application by adapting the success model of information systems developed by DeLone and McLean (1992) and Myers (1997). This research was conducted at PT Petrokimia Kayaku, Gresik. Sampling technique in this research is purposive sampling. The type of data in this study is the primary data obtained through questionnaires. The analysis tool used by researchers is SmartPLS 2.0 and the number of respondents as many as 40 employees who use Sevensofth Accounting in its operational activities. The results of data analysis indicate that the quality of service, quality of information systems and quality of information have a positive relationship to user satisfaction Sevensofth Accounting software. This research also proves that user satisfaction of Sevensofth Accounting has a positive effect on individual performance at PT Petrokimia Kayaku, Gresik.Keywords: Service quality, information quality, system quality, satisfaction of Sevensofth AccountingÂ user, and individual performance